-8t+(-5)+(-t)+1=

Simple and best practice solution for -8t+(-5)+(-t)+1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8t+(-5)+(-t)+1= equation:


-8t+(-5)+(-t)+1=0

We simplify the equation to the form, which is simple to understand
-8t+(-5)+(-t)+1=0

Remove unnecessary parentheses
-8t-5+(-t+)+1=0

Remove unnecessary parentheses
-8t-5-t+1=0

We move all terms containing t to the left and all other terms to the right.
-8t-1t=0+5-1

We simplify left and right side of the equation.
-9t=+4

We divide both sides of the equation by -9 to get t.
t=-0.444444444444

See similar equations:

| 12w+15w-9+5=-3w+5-9 | | 8(w-1)-(2+2w)=5w | | 10(3x+2)=80 | | 5w=12.5 | | 5x+7=9x-63 | | 28=.5*7h | | x^2+9x+24=0 | | -9y=18 | | 12x+9=7x+16 | | 4s^2-12sd+9d^2= | | 16t^2+0.25=0 | | (7y+3)(7y+3)+81=0 | | 7x+12=4x+13 | | 4p+5p=18 | | 5=2(x-2)+5-x | | 6m-8=2+2+9m-1 | | 13=3(x-3)-(x-8) | | 1.25-0.5h=h/2 | | (55b+1175)+(28b+3700)=53015 | | 3x=(2x-2)(m+7) | | 5+45=130 | | 4a=6-b | | 9y+5=8y-5 | | -5a+6=2(3a+8) | | 5+8(3-1)= | | -8y+4x=16 | | 2x+5=-3x+10 | | x-55=1987 | | -4.9x^2+43.4x=0 | | 19m+5-(-m)+c-7c= | | -8+(-14)=-80y+20+81y | | 2(5x+1)=2x-6x |

Equations solver categories